Analysis of The Quality of The Population And Civil Registration Service System In Ogan Ilir Regency Using Importance Performance Analysis Method (IPA) - Alfiatussyuaidah, Siti; Putra, M. Soekarno (IT Journal Research and Development, 2022)
To determine the quality of the Population Administration and Civil Registration Service website in Ogan Ilir Regency and to determine the level of user satisfaction in this study, the Importance Performance Analysis (IPA) method with a descriptive quantitative approach was used. The variable dimension for the questionnaire used is the E-GovQual (E-Government Quality) method which consists of 5 variables, namely ease of use, trust, reliability, content and appreance of information system, and citizen support distributed to 99 respondents. The IPA method itself has 3 stages of analysis, namely GAP analysis, conformity analysis, and Cartesian diagrams then the data is processed using IBM SPSS version 25. The results of this study indicate that the main priority in improvement is indicators no. 3 and 11. With gap analysis, 17 negative indicators are obtained. and 5 positive indicators which means that almost all attributes have not met user expectations. While the average value of the level of conformity is 97%, which means users are not satisfied with the performance of Admindukcapil services because the value of the level of conformity is <100%. Analysis, Service Quality, Importance Performance Analysis, E-Govqual.